Reforme in slovenska knjiga ali knjiga kot reforma? - Grilc, Uroš (Knjižnica, 2006)
The article tries to outline schematically the momentary state in the Slovenian publishing on the basis of data which one can compare with data we can get about publishing market in other European countries. The article continues trying to get a rough picture of the influence that submitted economic and social reforms could have on the publishing field. It also points to the importance of the book as the particular media of knowledge, creativeness and information in relation to media, competitive to book. All these statements are the starting-point to base the linkage between the development of the society and the book as an indispensable supposition of this development.
Keywords: bibliotekarstvo; library science; javni interes; založništvo; kulturna politika; Slovenia; Slovenija; European Union; Evropska unija